Pengembangan Media Dakwah Berbasis Digital di Pimpinan Ranting Muhammadiyah Kebonsari Jember - Daryanto Daryanto; Habibatul Azizah Al Faruq (Abdimas Mandalika, 2026)
Abstract:  PRM Kebonsari has not yet developed digital preaching and remains limited by its members' skills in managing digital content, so its outreach only reaches congregants who attend in person. It is therefore essential to develop a digital-based preaching platform to enable broader outreach. The objective of this community service program is for the Unmuh Jember service team to develop social media as a digital preaching platform and provide training in social media management for PRM Kebonsari as a partner. The platforms used in this program include Instagram, Facebook, and YouTube. The stages of this service program consist of preparation, the establishment of social media as a digital preaching platform, and training in digital religious content management. The results of this community service program indicate that the PKM Team successfully developed digital-based preaching by utilizing social media, including Instagram, Facebook, and YouTube. As a result, PRM Kebonsari now has official social media accounts, and human resource understanding and skills in managing social media content improved by an average of 61.75% (content design 65% and content uploading 67%), with 100% of participants able to upload preaching content independently by the end of the program.Abstrak: PRM Kebonsari belum mengembangkan dakwah secara digital dan masih terbatas pada kemampuan anggota dalam mengelola konten digital, sehingga jangkauan dakwah hanya menjangkau jamaah yang hadir langsung. Oleh karena itu, diperlukan pengembangan sarana dakwah berbasis digital agar penyampaian dakwah dapat dilakukan secara lebih luas. Tujuan program pengabdian ini adalah tim pengabdian Unmuh Jember akan mengembangkan media sosial sebagai sarana dakwah berbasis digital dan memberikan pelatihan pengelolaan media sosial bagi PRM Kebonsari sebagai mitra. Dalam hal ini, platform yang akan digunakan adalah media sosial Instagram, Facebook, dan Youtube. Tahapan yang dilakukan pada pengabdian ini dimulai dari persiapan, pembuatan social media sebagai sarana dakwah berbasis digital, dan pelatihan pengelolaan konten dakwah digital. Menghasilkan pengabdian bahwa Tim PKM dapat mengembangkan dakwah berbasis digital dengan memanfaatkan sosial media meliputi: Instagram, Facebook, dan Youtube. Sehingga PRM Kebonsari saat ini telah memiliki akun resmi sosial media. Pemahaman dan keterampilan sumber daya manusia dalam mengelola konten sosial media meningkat dengan rata-rata sebesar 61,75% (desain konten 65% dan pengunggahan konten 67%), serta 100% peserta mampu mengunggah konten dakwah secara mandiri pada akhir kegiatan.